HUBUNGAN STATUS GIZI DAN OLAHRAGA DENGAN KEJADIAN DISMENORE - Lona, Rizky Putri (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
As much as 60% - 95% women of reproductive ages had. Dysmenorrhea that it caused loss of employment, interfere learning activities at the school and family life. As much as 57,8% of schoolgirl in SMA I had dysmenorrhea. Many factors that caused of dysmenorrhea, such as nutritional status and exercise habits. Aims of this research were to find out relationship between nutritional status and exercise habits with dysmenorrhea to the schoolgirl in MAN I of Bengkulu City. This research used cross sectional design. Population were all schoolgirl in MAN I of Bengkulu City in 2012. Total of samples were 211 responden, it taken with simple random sampling. The data analyzed univariate and bivariate. Results of research showed that most of schoolgirl had dysmenorrhea (57,8%), schoolgirl had abnormal of nutritional status (42,7%), schoolgirl had less of exercise habits (37,4%). Result of bivariate showed that there was relationship between nutriotional status and exercise habits with incident of dysmenorrhea (p=0,000)